La gestión de marketing y las ventas de la empresa Almacenes León de la cuidad de Riobamba. - Basantes Morales, Marcela Salome (2023)
The present study addressed marketing management and its impact on sales in Almacenes León, located in Riobamba City. The main motivation for this research stemmed from the need to deeply understand how marketing management influences this company's sales and its commercial success. The study's overall objective was to determine the incidence of marketing management rigorously and systematically on Almacenes León's sales. The hypothetical deductive method was applied to achieve this goal, which was structured around three interconnected specific objectives. Firstly, a thorough diagnosis of the current marketing management and sales situation at Almacenes León was conducted to identify strengths and areas for improvement. Subsequently, a solid theoretical foundation was established, providing a robust conceptual basis for understanding marketing management and sales in the context of this specific company. This phase allowed for establishing connections between theory and practice, essential for formulating appropriate marketing management strategies, the third specific objective. The results obtained from the research supported the hypothesis, conclusively demonstrating that marketing management significantly impacts Almacenes León's sales. Furthermore, specific, and effective marketing management strategies were developed, tailored to the needs and characteristics of the company, representing a significant advancement in improving its performance in the Riobamba market.